Nuevos estudios geoquímicos de las Formaciones Lonco trapial y Garamilla y su interpretación en el contexto de patagonia septentrional - Zaffarana, Claudia Beatriz (2019)
In Early to Middle Jurassic times, the Chon Aike Volcanic Province was erupted in Patagonia during the Gondwana breakup stage. New geochemical analyses were obtained from Lonco Trapial and Garamilla Formations, volcanic rocks which belong to this magmatic province. Their geochemical features are typical of subduction environments, but some trace elements ratios and mineral compositions are compatible with intraplate magmas as well. Intermediate rocks are moderately enriched in LREE, are almost devoid of negative Eu anomalies and show a moderate fractionation in their HREE ([La/Sm]N=2,21-5,04; Eu/Eu*=0,81-1,32 and [Gd/Yb]N=1,40-3,06). The acidic rocks, in turn, are more enriched in LREE, whereas the HREE are almost unfractionated ([La/Sm]N=3.26-6.51, [Gd/Yb]N=1.27-1.79). The andesites from Lonco Trapial Formation have 87Sr/86Sr initial relationships between 0.7056 and 0.7064, negative initial ɛNd (average -3.78), and TDM of 1.3 Ga. Isotopic data point out to reworking of crustal rocks of mesoproterozoic age in the genesis of the central volcanic belt of Northern Patagonia.